(untitled) (Research, Society and Development, 2019)
The objective of this study is to perform a systematic review of the literature on the performance evaluation of countries in Olympic Games, specifically analyzing studies that encompass the non-parametric technique Data Envelopment Analysis (DEA). The scientific articles are dated from 2002 to 2018. It was necessary to organize the evolution of applied mathematical models and analyze the results in the game evaluation process. In addition, it was observed that the variables used and other techniques that helped the authors in the evaluation performed. A trend has been identified in the most recent literature for the use of the DEA model in networks. In general, countries are found to suffer from higher efficiency scores, especially at the administrative level. Therefore, after this type of dissemination of knowledge, it is possible to identify the need to remodel and implement new resource allocation strategies in order to obtain better performance indices in games of this magnitude.